Transformation of Islamic Geometric Principles and Symbolic Colors in the Design of the Sign System at Ribath Al-Falah Islamic Boarding School, Mataram City- West Nusa Tenggara - Azhari, Ridho Fidhi; Dinata, Ramanda D.S.; Hendrawan, Freddy (Journal of Visual Communication Design, 2026)
Sign systems in Islamic educational environments are often designed primarily as navigational tools, while Islamic identity is applied only as decorative ornamentation. This study develops a contextual sign system for Pondok Pesantren Ribath Al-Falah, Mataram City, through a geosemiotic visual transformation approach integrating Islamic geometry, symbolic color, and bilingual typography. The novelty of this study lies in positioning Islamic geometric principles not merely as aesthetic elements, but as structural components regulating hierarchy, modularity, and visual consistency within the signage system. The research responds to navigation difficulties and low environmental visibility identified through questionnaires, field observations, and user responses within the pesantren environment. A descriptive qualitative method was employed using a Design Thinking framework supported by Charles Sanders Peirce’s semiotic theory. Islamic geometric patterns, symbolic green color, and Arabic–Latin typography were transformed into a modular Environmental Graphic Design system consisting of directional, identification, and regulatory signage. The findings indicate that repetitive geometric structures, modular layouts, and consistent information hierarchy contribute to symbolic representation and navigational communication simultaneously. User evaluations also suggested positive responses regarding legibility, visibility, and semantic clarity of the proposed signage system. Overall, this study contributes a contextual Environmental Graphic Design approach integrating Islamic visual identity and wayfinding communication within Islamic educational environments.